2009
DOI: 10.4076/1757-1626-2-8101
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of horizontal root fracture: a case report

Abstract: Radicular fractures in permanent teeth are uncommon injuries among dental traumas, being only 0.5-7% of the cases. Traumatic dental injuries occur more frequently in young patients, and vary in severity from enamel fractures to avulsions.The magnitude of these problems is confirmed by statistical data on the prevalence of dental trauma during childhood and adolescence.Fracture occurs often in the middle-third of the root and rarely at the apical-third. The present paper reports a clinical case of a horizontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Several studies have reported that rigid splinting must be maintained for 2-3 months [ 3 , 16 ]; however, the effect of the splinting period on prognosis has not yet been determined [ 18 ]. In our case, right and left maxillary teeth had severe mobility and dislocation, and the 2-month duration of the fixed appliance was considered safe and viable for healing.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that rigid splinting must be maintained for 2-3 months [ 3 , 16 ]; however, the effect of the splinting period on prognosis has not yet been determined [ 18 ]. In our case, right and left maxillary teeth had severe mobility and dislocation, and the 2-month duration of the fixed appliance was considered safe and viable for healing.…”
Section: Discussionmentioning
confidence: 99%
“…Fraturas localizadas entre o terço médio e apical da raiz possuem melhor prognóstico quanto à sobrevivência da polpa e cicatrização dos fragmentos entre si quando comparada às fraturas localizadas próximo ao terço cervical. Isso acontece, principalmente, em virtude da comunicação do terço coronal da raiz com a cavidade oral e a subsequente contaminação microbiana da polpa ocasionando a necrose pulpar 17 .…”
Section: O Fratura Coronorradicularunclassified